Highly compressible porous carbon composite material, preparation method and application thereof

CN122897405APending Publication Date: 2026-10-13SHENZHEN GOLD MEDAL NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611324768.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-28
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的在于提出了一种铌酸钛/多孔碳复合材料的制备方法,旨在解决现有多孔碳的在抗压能力偏差及电子导电率低的问题

Benefits of technology

(1)抗压强度提升:本发明将预先烧制的多孔TiNb2O7,通过液相法与多孔碳前驱体混合,碳化,活化,制备出铌酸钛/多孔碳复合体,采用该抗压能力强的多孔TiNb2O7包覆多孔碳基体,从根本上提升了多孔碳基体的抗压强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122897405A_ABST
    Figure CN122897405A_ABST
Patent Text Reader

Abstract

The application discloses a kind of high pressure-resistant porous carbon composite material and preparation method and application thereof, belong to lithium ion battery negative electrode material technical field.The method includes: according to the molar ratio Ti:Nb=1:(1.5-2) titanium source and niobium source are weighed, foaming agent and binder are added, ball milling, drying, calcination, and TiNb2O7 is obtained;TiNb2O7 is dispersed in ethyl silicate solution;Porous carbon precursor and organic alkali catalyst are added to the dispersion, and after spray drying, pre-carbonization, high-temperature steam activation, titanium niobate / porous carbon composite material is obtained.The composite material utilizes the structural stability and large interlayer distance of titanium niobate itself, improves the compressive strength of porous carbon material, reduces the expansion of porous carbon material and improves the ion diffusion coefficient;Amorphous carbon generated by catalyst improves the bonding force between porous carbon and titanium niobate.The obtained material is applied to silicon-carbon material, which has the characteristics of strong pressure resistance, good rate performance and good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of porous carbon material preparation technology, and in particular to a high compressive strength porous carbon composite material, its preparation method and application. Background Technology

[0002] The improvement of lithium-ion battery performance is highly dependent on breakthroughs in anode materials. Silicon-carbon anodes have attracted much attention due to their high specific capacity, but the volume expansion during charge and discharge processes can easily lead to electrode pulverization and rapid capacity decay.

[0003] Porous carbon, as a key matrix for silicon-carbon materials, directly affects the expansion rate and specific capacity of electrodes due to its compressive strength and pore volume. However, current mainstream porous carbon matrix suffers from low compressive strength, poor electronic conductivity, and small interlayer spacing, leading to increased expansion and slow ion diffusion during charge and discharge, ultimately resulting in decreased cycle and rate performance.

[0004] To address the aforementioned issues, existing technologies attempt to improve these properties through surface coating or doping with ionic compounds. However, such methods are often complex, suffer from poor interfacial contact, and the coating layer can easily block ion channels, making it difficult to simultaneously achieve the compressive strength, ion diffusion coefficient, and electronic conductivity of porous carbon. Therefore, there is an urgent need to develop a composite material preparation method that can simultaneously improve these properties. Summary of the Invention

[0005] The purpose of this invention is to propose a method for preparing titanium niobate / porous carbon composite materials, aiming to solve the problems of poor compressive strength and low electronic conductivity in existing porous carbon materials. This invention improves the compressive strength and increases the interlayer spacing of porous carbon materials by coating the surface of porous carbon with titanium niobate, utilizing the structural stability of titanium niobate itself, while reducing the expansion of silicon-carbon materials and improving the ion diffusion coefficient.

[0006] This invention provides a method for preparing a high-compression-strength porous carbon composite material: Porous TiNb2O7 is dispersed in a silicate ester solution to form a TiNb2O7 dispersion; a porous carbon precursor and an organic base catalyst are added to the TiNb2O7 dispersion, and after being mixed evenly, the mixture is spray-dried, pre-carbonized, and activated with steam to obtain a titanium niobate / porous carbon composite material.

[0007] Furthermore, in the above technical solution, the preparation method of porous TiNb2O7 is as follows: titanium source and niobium source are weighed according to the molar ratio of titanium to niobium of 1:(1.5-2), foaming agent, binder and ethanol are added, and porous TiNb2O7 material is obtained by ball milling, drying and calcining in sequence.

[0008] Furthermore, in the above technical solution, the porous TiNb2O7 material is a pure-phase porous TiNb2O7 material.

[0009] Furthermore, in the above technical solution, the titanium source is titanium dioxide, the niobium source is niobium oxide; the foaming agent is one of azodicarbonamide, diethyl azodicarbonate, azodicyclohexanenitrile, dibenzyl azodihydroxy acid, or azobenzenesulfonic acid; and the binder is one of lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, or styrene-butadiene rubber.

[0010] Furthermore, in the above technical solution, the total mass ratio of the titanium source and niobium source to the foaming agent, binder and ethanol is 100:(5-20):(1-5):(100-500); the calcination temperature is 800-1200℃ and the time is 1-6h.

[0011] Furthermore, in the above technical solution, the silicate ester is ethyl silicate; the mass concentration of the TiNb2O7 dispersion is 1-10wt%.

[0012] Furthermore, in the above technical solution, the mass ratio of the porous TiNb2O7, the porous carbon precursor, and the organic base catalyst is (1-5):100:(1-5).

[0013] Furthermore, in the above technical solution, the porous carbon precursor is an amino resin, selected from one of urea-formaldehyde resin, melamine-formaldehyde resin, or benzo-melamine-formaldehyde resin; the organic base catalyst is selected from one of tetramethylguanidine, 4-dimethylaminopyridine, triethylamine, or pyridine.

[0014] Furthermore, in the above technical solution, the pre-carbonization temperature is 300-500℃ and the time is 1-6h; the steam activation temperature is 900-1300℃, the steam flow rate is 100-500mL / min, and the activation time is 60-600min.

[0015] Furthermore, in the above technical solution, a heating process is also included between the pre-carbonization and steam activation, and the final temperature of the heating process is 900-1300℃.

[0016] This invention provides a high-compression-strength porous carbon composite material obtained by the above preparation method. The composite material includes a porous carbon matrix and porous TiNb2O7 coated on the surface of the porous carbon matrix. The porous TiNb2O7 and the carbon matrix are bonded together by amorphous carbon. The high-compression-strength porous carbon composite material is a titanium niobate / porous carbon composite material.

[0017] Furthermore, in the above technical solution, the compressive strength of the composite material is 350-550 MPa, and the specific surface area is 1500-1800 m². 2 / g, pore volume 0.9-1.1cm 3 / g.

[0018] The present invention further provides the application of the above-mentioned high compressive strength porous carbon composite material as a precursor matrix for silicon-carbon materials.

[0019] Furthermore, in the above technical solution, the application is as an active material for the negative electrode of a lithium-ion battery.

[0020] The embodiments of the present invention have the following beneficial effects: (1) Improved compressive strength: The present invention uses pre-fired porous TiNb2O7 to mix with porous carbon precursor through liquid phase method, carbonize and activate it to prepare titanium niobate / porous carbon composite. The porous carbon matrix is ​​coated with this porous TiNb2O7 with strong compressive strength, which fundamentally improves the compressive strength of the porous carbon matrix.

[0021] (2) Improved ion diffusion coefficient: TiNb2O7 has a large interlayer spacing and its crystal structure has a wide lithium ion diffusion channel, which creates a fast ion transport channel in the composite material and improves the ion diffusion coefficient.

[0022] (3) Enhanced interfacial bonding: In this invention, an organic base catalyst is introduced into the liquid phase method to catalyze the carbon matrix and generate amorphous carbon active groups on the surface, which enhances the bonding force between porous carbon and titanium niobate, making it easier to mix with TiNb2O7, thereby improving the dispersion uniformity and tap density of the composite material. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] in: Figure 1 The image shows a SEM image of the titanium niobate / porous carbon composite prepared in Example 1. Detailed Implementation

[0025] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application belongs. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to be limiting of the application.

[0027] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0028] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0029] In this application, if the unit of a data range is only followed by the right endpoint, it means that the units of the left and right endpoints are the same.

[0030] In this application, terms such as "multiple," "various," and "repeatedly" are used unless otherwise specified, referring to a quantity greater than or equal to 2. For example, "multiple" means two or more. This document only specifically discloses some numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0031] The "scope" disclosed in this application is defined by a lower limit and an upper limit. A given scope is defined by selecting a lower limit and an upper limit, which define the boundaries of the specific scope. The scope defined in this way may include end values ​​or not.

[0032] Unless otherwise specified, the temperature parameters in this application may be either constant temperature processing or processing within a certain temperature range. The constant temperature processing allows for temperature fluctuations within the precision range controlled by the instrument.

[0033] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions. Unless otherwise specified, all technical features and optional technical features of this application can be combined to form new technical solutions.

[0034] Unless otherwise specified, all steps of this application may be performed sequentially or randomly, but sequentially is preferred.

[0035] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of this application.

[0036] Example 1 A method for preparing a high-compression-strength porous carbon composite material includes the following steps: Weigh 100g of titanium dioxide and 165g of niobium oxide and mix them evenly. Add 26.5g of azodicarbonamide, 7.95g of lithium carboxymethyl cellulose and 530g of ethanol and ball mill. Dry the mixture and then calcine the resulting material at 1050℃ for 3 hours to obtain porous TiNb2O7. 3g of porous TiNb2O7 was added to 27g of ethyl silicate solution and dispersed evenly to prepare a solution with a mass concentration of 10wt%. Then, 100g of urea-formaldehyde resin and 3g of tetramethylguanidine were added and mixed evenly. The mixture was spray-dried and then transferred to a tube furnace and pre-carbonized at 400℃ for 3h. After that, the temperature was raised to 1150℃ and activated for 300min by passing water vapor at a flow rate of 300ml / min to obtain titanium niobate / porous carbon composite.

[0037] Example 2 A method for preparing a high-compression-strength porous carbon composite material includes the following steps: Weigh 100g of titanium dioxide and 150g of niobium oxide and mix them evenly. Then add 12.5g of diethyl azodicarbonate, 2.5g of sodium carboxymethyl cellulose and 100g of ethanol, ball mill and dry. Then calcine the resulting material at 800℃ for 6 hours to obtain porous TiNb2O7. 1g TiNb2O7 was added to 99g ethyl silicate solution and dispersed evenly to prepare a solution with a mass concentration of 1wt%. Then, 100g melamine-formaldehyde resin and 1g 4-dimethylaminopyridine were added and mixed evenly. The mixture was then spray-dried and transferred to a tube furnace for pre-carbonization at 300℃ for 6h. The temperature was then raised to 900℃ and activated for 600min by introducing steam at a flow rate of 100ml / min to obtain titanium niobate / porous carbon composite.

[0038] Example 3 A method for preparing a high-compression-strength porous carbon composite material includes the following steps: Weigh 100g of titanium dioxide and 200g of niobium oxide and mix them evenly. Then add 60g of azobiscyclohexanenitrile, 15g of styrene-butadiene rubber and 500g of ethanol, ball mill and dry. Then calcine the obtained material at 1200℃ for 1 hour to obtain porous TiNb2O7 material. 5g of TiNb2O7 material was added to 95g of ethyl silicate solution and dispersed evenly to prepare a solution with a mass concentration of 5wt%. Then, 100g of benzo-melamine-formaldehyde resin and 5g of triethylamine were added and mixed evenly. The mixture was then spray-dried and transferred to a tube furnace for pre-carbonization at 500℃ for 1h. The temperature was then raised to 1300℃ and activated for 60min by introducing steam at a flow rate of 500ml / min to obtain titanium niobate / porous carbon composite.

[0039] Comparative Example 1: Unlike Example 1, TiNb2O7 was not added; otherwise, it was the same as Example 1.

[0040] Comparative Example 2: Unlike Example 1, azodicarbonamide is not added in step S1, but everything else is the same as in Example 1.

[0041] Comparative Example 3 Unlike Example 1, instead of coating the porous carbon surface with titanium niobate in one step, the titanium niobate was deposited on the surface of the porous carbon precursor via chemical precipitation, and then activated and carbonized to prepare the titanium niobate / porous carbon composite material. The preparation method is as follows: Weigh 100g of titanium dioxide and 165g of niobium oxide and mix them evenly. Add 26.5g of azodicarbonamide and 1000g of urea-formaldehyde resin and disperse them evenly. Then transfer the resulting material to a tube furnace and pre-carbonize it at 400℃ for 3h. After that, raise the temperature to 1150℃ and activate it by passing water vapor at a flow rate of 300ml / min for 300min to obtain titanium niobate / porous carbon composite.

[0042] Comparative Example 4 A method for preparing a high-compression-strength porous carbon composite material includes the following steps: Weigh 100g of titanium dioxide and 165g of niobium oxide and mix them evenly. Add 26.5g of azodicarbonamide, 7.95g of lithium carboxymethyl cellulose and 530g of ethanol, ball mill and dry. Then calcine the obtained material at 1050℃ for 3 hours to obtain porous TiNb2O7 material. 20g of porous TiNb2O7 material was added to 180g of ethyl silicate solution and dispersed evenly to prepare a solution with a mass concentration of 10wt%. Then, 100g of urea-formaldehyde resin and 3g of tetramethylguanidine were added and mixed evenly. The mixture was then spray-dried and transferred to a tube furnace for pre-carbonization at 400℃ for 3h. The temperature was then raised to 1150℃ and activated for 300min by introducing steam at a flow rate of 300ml / min to obtain titanium niobate / porous carbon composite.

[0043] Performance testing 1. Scanning electron microscopy (SEM) test: SEM images of the titanium niobate / porous carbon composite prepared in Example 1 were obtained. Figure 1 As can be seen, the material exhibits a granular structure with a uniform size distribution and a particle size between 5 and 10 μm.

[0044] 2. Physicochemical and button cell tests: 2.1 Physicochemical property testing: The pore volume and pore size of the porous carbon composite materials obtained in Examples 1-3 and Comparative Examples 1-4 were tested according to the national standard GB / T-38949-2020 "Determination of Pore Size of Porous Membranes - Standard Particle Method". The powder tap density and specific surface area of ​​silicon carbide were tested according to the national standard GB / T38823-2020 "Silicon Carbide". The powder conductivity of each porous carbon material was tested using a four-probe tester. The diffusion coefficient of the material was tested using GITT. Simultaneously, the crush strength of the material was tested using a compressive strength tester, applying pressure at a rate of 5 mm / min until the material collapsed. The pressure changed instantaneously, and the highest pressure was recorded as the crush strength.

[0045] The test results are shown in Table 1.

[0046] 2.2 Button Cell Battery Performance Test: The porous carbon composite materials corresponding to Examples 1-3 and Comparative Examples 1-4 were used as negative electrode materials for lithium-ion batteries to prepare coin cells according to the following method: A binder, conductive agent, and solvent were added to the corresponding porous carbon composite materials, stirred to form a slurry, coated onto copper foil, and dried and rolled to obtain a negative electrode sheet. The binder used was LA132, the conductive agent was SP (conductive carbon black), and the solvent was NMP. The ratio of porous carbon composite material: SP:LA132:NMP was 70g:15g:15g:300mL. The electrolyte was a solution with LiPF6 as the electrolyte and a concentration of 1mol / L. The solvent was a mixture of EC and DEC with a volume ratio of 1:1. The lithium metal sheet was used as the counter electrode, and the separator was a polypropylene (PP) membrane.

[0047] Each coin cell was assembled in an argon-filled glove box, and then the following performance tests were performed: Electrochemical performance test: Specifically, the electrochemical performance was performed on the Wuhan Landian CT2001A battery tester, with a charge / discharge voltage range of 0.005V to 1.5V and a charge / discharge rate of 0.1C. The discharge specific capacity and initial efficiency of the corresponding coin cell were tested. At the same time, the room temperature charge DCR (50% SOC) and cycle performance (0.1C / 0.1C, 100 cycles) of the corresponding coin cell were tested; and the full charge expansion of the negative electrode was also tested.

[0048] The test results are shown in Table 2.

[0049] Table 1 As shown in Table 1, doping with porous TiNb2O7 in the examples improves the compressive strength of the materials. The strength of Examples 1-3 is much higher than that of Comparative Example 1. This is because TiNb2O7 has a rigid structure, which significantly enhances its resistance to expansion. Although the strength of Comparative Example 2 is higher than that of Comparative Example 1, it is still lower than that of the examples, indicating that dense TiNb2O7 alone is not enough. The key to improving the compressive strength lies in the porous TiNb2O7 formed by the foaming agent. At the same time, the large pore size of TiNb2O7 increases the pore volume of the porous carbon composite material, constructing a "three-dimensional conductive network" and significantly reducing the internal resistance. Compared with Example 1, Comparative Example 3 does not coat the porous carbon surface with titanium niobate in one step, resulting in poor coating uniformity, poor structural density, reduced compressive strength and tap density, and higher impedance due to poor uniformity. Compared with Example 1, Comparative Example 4 has an excessively high porosity of TiNb2O7, which reduces the specific surface area, pore volume, and pore size of the material.

[0050] Table 2 As can be seen from Table 2, Examples 1-3 have excellent diffusion coefficients and high first-time efficiency. This is because the doping of TiNb2O7 in the materials of these examples increases the ion diffusion rate of the materials and reduces defects, thereby improving the first-time efficiency and rate performance.

[0051] As can be seen from the examples and comparative examples, neither coating the porous TiNb2O7 material nor using non-foamed TiNb2O7 material yields only limited performance improvements. However, when pre-sintered porous TiNb2O7 material is used in synergy with an organic base catalyst, the performance improvement far exceeds the combined effect of the two catalysts alone, confirming the synergistic effect between the two core inventive points of this invention. Furthermore, the method of first preparing porous TiNb2O7 and then coating it onto the surface of a porous carbon precursor exhibits better structural stability and coating uniformity than directly depositing and sintering niobium oxide and titanium oxide onto the porous carbon surface to generate TiNb2O7, which is beneficial for improving cycle performance.

[0052] The applicant declares that the present invention is illustrated by the above embodiments, but the present invention is not limited to the above process steps, that is, it does not mean that the present invention must rely on the above process steps to be implemented. Those skilled in the art should understand that any improvements to the present invention, equivalent substitutions of the raw materials used in the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

[0053] The above description discloses only preferred embodiments of the present invention and should not be construed as limiting the scope of the present invention. Therefore, equivalent variations made in accordance with the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing a high-compression-strength porous carbon composite material, characterized in that, Porous TiNb2O7 is dispersed in a silicate ester solution to form a TiNb2O7 dispersion; a porous carbon precursor and an organic base catalyst are added to the TiNb2O7 dispersion, and after being mixed evenly, the mixture is spray-dried, pre-carbonized, and activated with steam to obtain a titanium niobate / porous carbon composite material.

2. The preparation method according to claim 1, characterized in that, The preparation method of porous TiNb2O7 is as follows: titanium source and niobium source are weighed according to the molar ratio of titanium to niobium of 1:(1.5-2), foaming agent, binder and ethanol are added, and porous TiNb2O7 is obtained by ball milling, drying and calcination in sequence.

3. The preparation method according to claim 2, characterized in that, The titanium source is titanium dioxide, and the niobium source is niobium oxide; the foaming agent is one of azodicarbonamide, diethyl azodicarbonate, azodicyclohexanenitrile, dibenzyl azodihydroxy acid, or azobenzenesulfonic acid; the binder is one of lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, or styrene-butadiene rubber.

4. The preparation method according to claim 2, characterized in that, The total mass ratio of the titanium source and niobium source to the foaming agent, binder and ethanol is 100:(5-20):(1-5):(100-500); the calcination temperature is 800-1200℃ and the time is 1-6h.

5. The preparation method according to claim 1, characterized in that, The silicate ester is ethyl silicate; the mass concentration of the TiNb2O7 dispersion is 1-10 wt%.

6. The preparation method according to claim 1, characterized in that, The mass ratio of the porous TiNb2O7, the porous carbon precursor, and the organic base catalyst is (1-5):100:(1-5).

7. The preparation method according to claim 1, characterized in that, The porous carbon precursor is an amino resin, selected from urea-formaldehyde resin, melamine-formaldehyde resin, or benzo-melamine-formaldehyde resin; the organic base catalyst is selected from tetramethylguanidine, 4-dimethylaminopyridine, triethylamine, or pyridine.

8. The preparation method according to claim 1, characterized in that, The pre-carbonization temperature is 300-500℃, and the time is 1-6 hours; The steam activation temperature is 900-1300℃, the steam flow rate is 100-500mL / min, and the activation time is 60-600min.

9. A high-compression-strength porous carbon composite material obtained by the preparation method according to any one of claims 1-8.

10. The application of the high compressive strength porous carbon composite material according to claim 9 as a precursor matrix for silicon-carbon materials.